TINJAUAN YURIDIS TERHADAP TINDAK PIDANA TANPA IZIN USAHA NIAGA (STUDI KASUS PUTUSAN NOMOR 149/PID.B/LH/2019/PN SRG) - Hartono; Yusuf M Said (The Juris, 2022)
Indonesia has so many natural resources. For example, there are gold mines, natural gas, petroleum, coal mines, spices, to the abundant underwater natural wealth. So that strict arrangements or regulations are needed for the protection of the utilization of mining goods in Indonesia. The problem in this paper is: What are the provisions of the article regarding oil and gas trading business permits in law number 22 of 2001 concerning oil and natural gas? And what is the basis for the consideration of the Panel of Judges of the Serang District Court Number 149/Pid.B/LH/2019/PN Srg? The research method used is a normative research method that focuses on library research to obtain secondary data from legal materials. The normative approach is carried out by reviewing the applicable provisions or laws and regulations. The results of the research show that as stated in Article 23 paragraph 1 of Law Number 22 of 2001 concerning Oil and Gas, it states that downstream oil and gas business activities can be carried out by business entities after obtaining business licenses from the government. Oil and Gas Business Permits for Downstream Business Activities in the form of Processing Business Permits, Transportation Business Permits, Storage Business Permits, and Trading Business Permits.